Some aspects of the abuse of rights in civil and economic proceedings - K. M. Hurtova (Law and Safety)
The article is devoted to the analysis of abuse of procedural rights in civil and economic proceedings. The views and approaches to the problem of abuse of rights available in the legal literature are considered.